2015
DOI: 10.1515/jcim-2014-0032
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of some selected fruit blends on testicular toxicity in alloxan-induced diabetic rats

Abstract: This study shows an improvement in testicular antioxidant activities and sperm qualities by single and double doses of the formulation, suggesting its protective potential against testicular toxicity in diabetic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…We believe that the increased prostatic CAT expression in the MH group may be induced in response to intrauterine oxidative stress. Although there is a lack of studies demonstrating the effect of GDM on offspring reproductive organs, we believe that our results can be related to those of Obode et al (), who demonstrated increased CAT activity in testes of alloxan‐induced diabetic in adult rats and associated these results with increased oxidative stress and reduced quality of sperm in diabetic rats.…”
Section: Discussionsupporting
confidence: 82%
“…We believe that the increased prostatic CAT expression in the MH group may be induced in response to intrauterine oxidative stress. Although there is a lack of studies demonstrating the effect of GDM on offspring reproductive organs, we believe that our results can be related to those of Obode et al (), who demonstrated increased CAT activity in testes of alloxan‐induced diabetic in adult rats and associated these results with increased oxidative stress and reduced quality of sperm in diabetic rats.…”
Section: Discussionsupporting
confidence: 82%
“…Alterations of these pathways have been implicated in the onset of macro‐ and microvascular diseases (Boden, ; Kilarkaje et al, ). Of particular interest is the impairment of the male reproductive system, which is characterized by peroxidation of the testicular PUFAs constituents, morphological changes in the testes, and erectile dysfunction among others (Kilarkaje et al, ; Obode et al, ; Xu et al, ). In this study, the therapeutic effect of Raffia palm wine was investigated in hyperglycaemia‐induced oxidative injury in T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Male infertility has been recognized as one of the complications of diabetes mellitus (DM) (Dias, Alves, Silva, & Oliveira, 2014;Kilarkaje, Al-Hussaini, & Al-Bader, 2014;Xu et al, 2014). This has been attributed to the polyunsaturated fatty acids (PUFAs)-rich content of the testicular tissues, which is highly susceptible to oxidative damage from hyperglycaemia-generated free radicals (Erukainure et al, 2012;Obode et al, 2015). Oxidative damage occurs when the generated free radicals overwhelms the testicular endogenous antioxidant system, leading to impaired spermatogenesis and steroidogenesis, and finally infertility (Alves et al, 2013;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies indicated that guavas have anti-inflammatory, anti-microbial, anti-oxidative, anticancer, and anti-diarrheal functions (25)(26)(27). Many studies have demonstrated that guavas can improve anti-oxidant functions such as glutathione levels and activities of superoxide dismutase, catalase, and glutathione peroxidase against oxidative stress-induced damage (28)(29)(30)(31). Guavas can inhibit arsenic-induced (29), streptozotocin-induced (30,31), and alloxan-induced (28) oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that guavas can improve anti-oxidant functions such as glutathione levels and activities of superoxide dismutase, catalase, and glutathione peroxidase against oxidative stress-induced damage (28)(29)(30)(31). Guavas can inhibit arsenic-induced (29), streptozotocin-induced (30,31), and alloxan-induced (28) oxidative stress. Furthermore, a recent study suggested that guavas can inhibit caspase activity to attenuate cell apoptosis in type II diabetic rats (32).…”
Section: Introductionmentioning
confidence: 99%